Implementación y desarrollo de práctica de automatización a través de un módulo didáctico con el PLC S7-1200 para simular variaciones de temperatura en un caldero. - Palomo Rogia, Wilson David (2017)
It was implemented and developed an automation practice through a didactic module with the PLC S7-1200 to simulate temperature variations in a cauldron in the research laboratory of the Electromechanical career of the Technical University of Cotopaxi Extension La Maná in the first Instance was determined the theoretical foundations necessary for the implementation establishing norms and parameters suitable for the appropriate use of the programmable logic controller, knowing that this is widely used in many industries and machines. Unlike general purpose computers, the PLC is designed for multiple input and output signals, extended temperature ranges, immunity to electrical noise, and resistance to vibration and impact. It was verified the operation of all the devices that were used in the implementation, building the metal base, all the devices were integrated, obtaining as a result the didactic module in which the students of the race can accede to realize automation practices recognizing the objectives Of the automation that are: to improve the productivity of the company, reducing the costs of the production and improving the quality of the same, toimprove the conditionsof work of the personnel, suppressing the risky works and increasing the security.